Factors influencing cart abandonment in South African fashion e-commerce - Mkhize, Sibusiso (University of the Witwatersrand, Johannesburg, 2025)
The rise of e-commerce has transformed consumer behaviour, but cart abandonment remains a significant challenge for online retailers. This study investigated the factors influencing cart abandonment among South African online fashion shoppers, framed within the conceptual frameworks of usability, security, and perceived price fairness. The research aimed to identify and analyse the drivers of cart abandonment, bridging gaps in existing literature by focusing on a developing market context. A quantitative approach, comprising a survey, was adopted. Data were collected from a sample of 400 online shoppers using a validated survey instrument and analysed using statistical methods, including regression analysis and Analysis of Variance (ANOVA). The quantitative analysis explored relationships between independent variables (website usability, perceived security, and perceived price fairness) and the dependent variable (cart abandonment). Key findings revealed that website usability significantly affects cart abandonment rates, emphasising the need for intuitive navigation and fast- loading pages. Perceived security was found to influence trust in online transactions, with shoppers prioritising platforms offering robust encryption and transparent data policies. Lastly, perceived price fairness emerged as a critical determinant, with hidden charges leading to higher cart abandonment. The study concludes that addressing these factors collectively can reduce cart abandonment rates and enhance customer retention. The findings provide actionable insights for e-commerce stakeholders and offer strategies for optimising online shopping experiences in South Africa. Future research should expand the scope to include cross-industry comparisons and explore emerging factors, such as environmental sustainability and personalisation, in e-commerce behaviour.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Cart Abandonment; E-commerce Behaviour; Online Shopping; South African Consumers; Fashion Retail; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure